Molecular Mechanisms of Ligand-Mediated Attenuation of DNA Binding by MarR Family Transcriptional Regulators - Perera, Inoka C.; Grove, Anne (My University, 2010)
Bacteria and archaea encode members of the large multiple antibiotic resistance regulator (MarR) family of transcriptional regulators. Generally, MarR homologs regulate activity of genes involved in antibiotic resistance, stress responses, virulence or catabolism of aromatic compounds. They constitute a diverse group of transcriptional regulators that includes both repressors and activators, and the conventional mode of regulation entails a genetic locus in which the MarR homolog and a gene under its regulation are encoded divergently; binding of the MarR homolog to the intergenic region typically represses transcription of both genes, while binding of a specific ligand to the transcription factor results in attenuated DNA binding and hence activated gene expression. For many homologs, the natural ligand is unknown. Crystal structures reveal a common architecture with a characteristic winged helix domain for DNA binding, and recent structural information of homologs solved both in the absence and presence of their respective ligands, as well as biochemical data, is finally converging to illuminate the mechanisms by which ligand-binding causes attenuated DNA binding. As MarR homologs regulate pathways that are critical to bacterial physiology, including virulence, a molecular understanding of mechanisms by which ligands affect a regulation of gene activity is essential. Specifying the position of ligand-binding pockets further has the potential to aid in identifying the ligands for MarR homologs for which the ligand remains unknown.
Keywords: MarR, ligand binding, transcription factor, DNA binding